Fault ride-through enhancement using an enhanced field oriented control technique for converters of grid connected DFIG and STATCOM for different types of faults. (May 2016) - Ananth, D.V.N.; Nagesh Kumar, G.V.
Abstract: With increase in electric power demand, transmission lines were forced to operate close to its full load and due to the drastic change in weather conditions, thermal limit is increasing and the system is operating with less security margin. To meet the increased power demand, a doubly fed induction generator (DFIG) based wind generation system is a better alternative. For improving power flow capability and increasing security STATCOM can be adopted. As per modern grid rules, DFIG needs to operate without losing synchronism called low voltage ride through (LVRT) during severe grid faults. Hence, an enhanced field oriented control technique (EFOC) was adopted in Rotor Side Converter of DFIG converter to improve power flow transfer and to improve dynamic and transient stability. A STATCOM is coordinated to the system for obtaining much better stability and enhanced operation during grid fault. For the EFOC technique, rotor flux reference changes its value from synchronous speed to zero during fault for injecting current at the rotor slip frequency. In this process DC-Offset component of flux is controlled, decomposition during symmetric and asymmetric faults. The offset decomposition of flux will be oscillatory in a conventional field oriented control, whereas in EFOC it was aimed to damp quickly. This paper mitigates voltage and limits surge currents to enhance the operation of DFIG during symmetrical and asymmetrical faults. The system performance with different types of faults like single line to ground, double line to ground and triple line to ground was applied and compared without and with a STATCOM occurring at the point of common coupling with fault resistance of a very small value at 0.001 Ω. Highlights: Enhanced field oriented control (EFOC) technique is developed to improve transient stability during and after fault. DC-Offset component of stator flux is controlled and the decomposition during asymmetric and symmetric faults and this component is oscillatory in a conventional FOC, whereas in EFOC it was aimed to damp quickly. Voltage mitigation is improved and surge currents are limited to enhance the operation of DFIG during symmetrical and asymmetrical faults. A STATCOM is coordinated to the system for obtaining much better stability and enhanced operation during grid fault. The system performance with different types of faults like single line to ground, double line to ground and triple line to ground faults is analyzed and compared without and with STATCOM.